Examining the links between burnout and suicidal ideation in diverse occupations - Oh, Dae Jong; Shin, Young Chul; Oh, Kang-Seob; Shin, Dong-Won; Jeon, Sang-Won; Cho, Sung Joon (Frontiers in Public Health, 2023)
Introduction It is uncertain whether burnout is associated with suicidal ideation among workers not in health care services. The aim of this study was to identify how burnout and suicidal ideation are linked among employees in various occupations and whether depression affects this link. Methods This cross-sectional study collected data from 12,083 participants aged 19–65 years from 25 companies and public institutions who underwent workplace mental health screening. Burnout and depression were assessed using both the Oldenburg Burnout Inventory and the Center for Epidemiologic Studies Depression Scale. Suicidal ideation was assessed by a self-rated questionnaire from the Korea National Health and Nutrition Examination Survey. Results Exhaustion but not the cynicism dimension of burnout was associated with increased odds of suicidal ideation after adjustment for depression and other covariates (odds ratio [OR] = 1.47, 95% CI = 1.26–1.72). The association of exhaustion with suicidal ideation was significant in both depressed (OR = 1.36, 95% CI = 1.14–1.61) and not depressed (OR = 1.77, 95% CI = 1.13–2.76) participants. In exhausted participants, insufficient job control, an unfavorable occupational climate, low educational level, and depression were associated with increased odds of suicidal ideation. Conclusion Exhaustion is linked with risk of suicidal ideation in employees not in health care service, regardless of depression status. Exhausted employees, particularly those having poor job resources, should be recognized as an at-risk group.